Efek nihil pembelajaran sebelumnya terhadap efikasi diri dan motivasi pada pembelajar bahasa jerman pemula - Aulia Azzahra Hidayah; Pepen Permana; Nur Muthmainah (Jurnal Konseling dan Pendidikan, 2025)
Prior learning experience is often assumed to influence students’ psychological readiness in foreign language education. This study examined whether first-year students in a tertiary German language education program differed in self-efficacy and learning motivation based on their prior exposure to German before university. Using a quantitative comparative approach, data were collected from 76 students through adapted measures of self-efficacy and academic motivation. The findings revealed no statistically significant differences between students with and without prior learning experience in either self-efficacy or motivation. Although a slight tendency in motivational scores favored the experienced group, effect sizes were small, indicating limited practical differences. These results suggest that, in the context of beginner-level tertiary German education, prior exposure alone may not function as a decisive differentiating factor in students’ initial psychological conditions. Instead, self-efficacy and motivation appear to be shaped in interaction with the immediate learning context. Further longitudinal research is recommended to explore how individual differences evolve over time in foreign language learning.